Peripherally inserted central catheters versus implantable port catheters for cancer patients: a meta-analysis - Lin, Li; Li, Wei; Chen, Chen; Wei, Anhua; Liu, Yu (Frontiers in Oncology, 2023)
Background: The implanted vascular access ports (PORTs) was compared with Peripherally inserted central catheters (PICCs) as the administration of chemotherapy regarding different clinical effects and adverse effects, and which is better is debatable. Hence, the current article was conduct to assess the safety efficacy of these two optimal vascular access strategies. Methods: The following electronic databases were searched: Pubmed, Embase, Cochrane library updated on May, 2023.Studies of the differences of complication rates in cancer patients using either a PICC or a PORT for chemotherapy were included. Meta-analysis Revman 5.3 software was used for statistical analysis. Results: A total of 22 articles were retrieved. The results suggested that PORT has superiority safety profile, with lower incidences of overall adverse effects (OR=2.72, 95%CI=1.56-4.72 P=0.0004), catheter-related thrombosis (OR=2.84, 95%CI=1.97-4.11, P＜0.00001) , and allergic reaction (OR=6.26, 95%CI=1.86-21.09, P=0.003) being higher than typically expected with the PICC. Moreover, PICC was non-inferior to the PORT group with respect to DVT (OR=2.00, 95%CI=0.86-4.65, P=0.11) and infection (OR=1.55, 95%CI=0.75-3.22, P=0.24). Conclusion: PORT did achieve safety benefit compared with those receiving chemotherapy through PICC. Therefore, the PORT regards as a safe and an effective vascular access as the administration of chemotherapy. While, when taking the economic factor and some key elements into consider, more high-quality researches would help to verify these clinical benefits.